A Critical Evaluation of Emecheta’s Portrayal of the Female Gender in Second Class Citizens - Oladipo, Temidayo David; Ogbeide-Ihama, Mojisola A. (African Journal of Stability and Development (AJSD), 2018)
This paper examines Buchi Emecheta’s The Second Class Citizens, focusing especially on her portrayal of women in two societies. It highlights women’s struggles with traditional patriarchal institutions to treat the travails of women during the postcolonial period. Textual analysis method is employed to engage themes like patriarchy, women’s oppression, gender discrimination, female independence and assertiveness, domestic violence, how the early set of women who emigrated to Europe from Nigeria after independence were treated, and how their potentials were (almost) stifled. The work concludes that although, unjustifiably, women are wrongly treated in society when they earn less, yet even when women are the breadwinners, the system is still not in their favour. Educating the girlchild is lauded alongside the need for continuous demand for social change as the solution to women’s ill-treatment in society. Educating the girl-child will ensure she is enlightened enough to question the many ills of society, so that she is not maltreated as a second class in her own society and foreign lands.